The Resilience Machine - Bohland, James R.; Davoudi, Simin; Lawrence, Jennifer L. (Milton : Routledge, 2018)
We live in a time where environmental pressures, social inequities and political derision are the backdrop of everyday life, and where resilience has become a routine prescription for coping with the conditions of modern existence. Drawing an analogy to Harvey Molotch's urban growth machine, this book explores different narratives of resilience and their policy and practice manifestations for cities, citizens and communities. It expands on the metaphor of the machine to show how resilience can be better understood as an assemblage. Bringing together authors from multiple disciplines and different parts of the world, the book unmasks the often invisible effects of resilience strategies by examining ways in which neoliberal mentalities are fed through the rhetoric of resilience practices, policies and development projects. The contributing essays provide provocative accounts of several areas of inquiry, including biopolitics and smart bodies, resilient cities and communities, urban planning and disaster management, justice and vulnerability, and resistance to resilience. Holding out hope for critical potentials in 'resilience, ' The Resilience Machine proposes to move beyond mechanisms of adaptation and into imagining what resilient life could look like in a more just, equitable and democratic world. The Resilience Machine is a current, vital addition to resilience, community and urban scholarship.
Urban Planning, System Thinking and Resilience in the Context of Rising ComplexitiesTowards a Critical Political Geography of Resilience Machines; Conclusions; Notes; References; 10. Resilience and Justice: Planning for New York City; New York's Resiliency Planning; Is the Term 'Resilience' Useful in Promoting Justice?; Adaptation to Threat; Countervailing Pressures; Conclusion; Notes; References; 11. Seeking the Good (Enough) City; Introduction; The Urban Age and Its Discontents; The Ruse of Catastrophism; Beyond Simple Secularism; Seeking the Good (Enough) City.
Conclusion: Resilience without Hope.
OCLC-licensed vendor bibliographic record.
Keywords: City planning; Sustainable development; Emergency management; Preparedness; POLITICAL SCIENCE -- Public Policy -- City Planning & Urban Development; SOCIAL SCIENCE -- Sociology -- Urban; ARCHITECTURE -- Urban & Land Use Planning